American spirit : profiles in resilience, courage, and faith - Kyle, Taya, 1974-; DeFelice, Jim, 1956- (William Morrow, an imprint of HarperCollinsPublishers, 2019)
After losing her husband, "American Sniper" Chris Kyle, bestselling author Taya Kyle entered a period of deep grief. And yet the experience served as a catalyst for profound growth. Taya found her own reserve of strength with the help of the generous love and support of family and friends<U+2014>and also many strangers across America, who selflessly shared their own stories of suffering, survival, and triumph. Inspired by her experience, Taya discovered her calling: spreading a message of how love, passion, and service can combine to help us persevere over personal pain and heal our communities. Working with trusted collaborator Jim DeFelice (coauthor of American Sniper and American Wife), Taya tells her own story, as well as those of other Americans who have built extraordinary lives after traveling down life<U+2019>s most difficult roads<U+2014>through loss, illness, all manner of setback. They embody the “American spirit” of resilience, faith, togetherness that has built the nation. American Spirit profiles more than 30 individuals, young and old, rich and not-so-rich, famous and unknown, who have overcome hardship and done extraordinary things for their communities and for the nation at large. The 9/11 survivor, badly burned over 60% of his body, who asked himself- What debt do I owe to God? And to my fellow human beings? What am I supposed to do with this miracle of survival? The man with the hole in his heart who runs ultramarathons. The young cancer victim whose lemonade stand inspired a revolutionary new model for fighting cancer. The blind cyclist; the pastor who became an undercover investigator, and more. In the end, these stories teach us how to find purpose and heal the world, no matter the difficulty. “Every action, big or small,” Taya writes, “has the potential to spark someone else<U+2019>s movement.”